Jumlah Pembiayaan Murabahah dengan Tenor Pembiayaan Terhadap Profitabilitas Bank BNI Syariah - Khori Muharani (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2020)
ABSTRACT This study aims to measure the impact of the effect of the amount of murabahah financing based on short and long-term financing tenors on profitability (ROA) at BNI Syariah KC Jambi City. Determine the amount of murabahah financing with a financing tenor based on the financing products offered by Islamic banks. The analysis method used is multiple linear regression, by performing the classical assumption test, T test, F test and R2 test. The analysis results show that partially the amount of murabahah financing with a financing tenor of 1-2 has a positive effect on profitability (ROA) with sig 0.019 <0.05. The variable of the amount of murabahah financing with a financing tenor of 3-5 years, and the amount of murabahah financing with a financing tenor of more than 5 years-20 years did not have a significant effect on profitability (ROA) with sig degrees 0.636> 0.05 and 0.146> 0.05. Simultaneous test (F test) of all independent variables has a significant effect on profitability (ROA) with a significance value of 0.007 <0.05. The coefficient of determination R Square is 52.2%, the effect between variables on ROA while the remaining 47.8% is influenced by other factors outside the research model. Keywords: Total Murabahah Financing; Tenor Financing; Profitability (ROA).